The Maddaloni/X-6 eruption stands out as one of the major events during the Late Pleistocene at Campi Flegrei - Giada Fernandez; Antonio Costa; Biagio Giaccio; Jacopo Natale; Danilo M. Palladino; Gianluca Sottili (Communications Earth & Environment)
Abstract The Campi Flegrei caldera (Italy) is among the most productive volcanoes of the Mediterranean area. However, the volcanic history preceding the VEI 7 Campanian Ignimbrite eruption (~40 ka) is still poorly constrained. Here, we use a tephra dispersal model to reconstruct the eruption source parameters of the Maddaloni/X-6 eruption (~109 ka), one of the most widespread Late Pleistocene Mediterranean marker tephra from Campi Flegrei. Our results suggest that the eruption was characterized by an early Plinian phase involving ~6 cubic kilometers (within the range of 3–21 cubic kilometers) of magma, followed by a co-ignimbrite phase erupting ~148 cubic kilometers (range of 60–300 cubic kilometers). This ranks the Maddaloni/X-6 as a high-magnitude (M7.6) eruption, resulting at least as the second largest known event from Campi Flegrei. This study provides insights into the capability of the Campi Flegrei magmatic system to repeatedly generate large explosive eruptions, which has broad implications for hazard assessment in the central Mediterranean area.